2010
DOI: 10.1007/s00508-010-1504-0
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive behaviour in Down syndrome: a cross-sectional study from childhood to adulthood

Abstract: Acquired equivalence (AE) is a form of feedback-based associative learning where the subject learns that two or more stimuli are equivalent in terms of being mapped onto the same outcomes or responses. While several studies dealt with how various neurological and psychiatric conditions affect performance on AE tasks (typically with small populations), studies dealing with AE in healthy subjects are rare, and no study has ever made an attempt to plot the development of this form of learning from the childhood t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 9 publications
3
31
1
Order By: Relevance
“…interpersonal skills), practical (e.g. activities of daily living), communication (e.g., language use), and motor skills (e.g., gross motor, fine-motor) learned and used by people so they can function in everyday living situations, has been widely studied in individuals with IDD and more specifically in individuals with DS (Dressler, Perelli, Feucht, & Bargagna, 2010; Dykens, Hodapp, & Evans, 2006). As a way of measuring strengths and weaknesses in daily functioning, assessing adaptive behavior in people with DS is critical for determining relations with cognitive abilities, quality of life, or level of independence.…”
Section: Resultsmentioning
confidence: 99%
“…interpersonal skills), practical (e.g. activities of daily living), communication (e.g., language use), and motor skills (e.g., gross motor, fine-motor) learned and used by people so they can function in everyday living situations, has been widely studied in individuals with IDD and more specifically in individuals with DS (Dressler, Perelli, Feucht, & Bargagna, 2010; Dykens, Hodapp, & Evans, 2006). As a way of measuring strengths and weaknesses in daily functioning, assessing adaptive behavior in people with DS is critical for determining relations with cognitive abilities, quality of life, or level of independence.…”
Section: Resultsmentioning
confidence: 99%
“…Extant literature on adaptive behavior of adults with DS reports low adaptive behavior levels for all domains and subdomains (Adams & Oliver, 2010;Di Nuovo & Buono, 2011;Dressler, Perelli, Feucht, & Bargagna, 2010;Witts & Elders, 1998). However, all studies used the Vineland Adaptive Behavior Scales (VABS) which complicates comparison.…”
Section: Adaptive Behaviormentioning
confidence: 99%
“…According to Sparrow et al (2005), when the Vineland-II was created, the VABS was considerably modified to increase the age-range, which was birth to 19 years old for the VABS (Sattler, 1992). Dressler et al (2010) reported low adaptive levels for 40 adults with DS over the age of 20 residing in Italy, however they reported age-equivalents rather than v-scale scores and standard scores, which makes direct comparison challenging. Another challenge was that Dressler et al separated the adults with DS into age groups of 20-30 years old and over 30 years old.…”
Section: Adaptive Behaviormentioning
confidence: 99%
See 2 more Smart Citations